Modern tocolytic therapy in treatment of threatening preterm birth (literature review) - A V Van; A S Kulikova; S A Zalesskaya; Yu E Dobrohotova (IP Berlin A.V., 2014)
This article touches upon the most important problem of obstetrics and neonatology - preterm birth. This article provides an analysis of the literature on the pathogenesis, etiology preterm birth, the role of modern therapy used in the treatment of preterm birth. Efficacy and safety this therapy for the mother and fetus. We analyzed various modes of tocolytic therapy, which used in modern obstetrics now. We provided data of foreign studies on the subject.